Severe childhood lichen planus pemphigoides after hepatitis A vaccination - M. Lahouel; A. Aounallah; S. Mokni; B. Sriha; C. Belajouza; M. Denguezli (Wiley, 2022)
Abstract Background Lichen planus (LP) pemphigoides (LPP) is a very rare autoimmune bullous disorder, that is, exceptional in children. Case Report We report a case of LP pemphigoides with severe cutaneous and mucosal involvement in an 8‐year‐old girl who consulted for multiple vesicular and bullous lesions associated with shiny erythematous‐purple plaques. The eruption occurred 2 months after vaccination against hepatitis A virus. The diagnosis of LP pemphigoides was confirmed by histopathology and immunofluorescence examination. The patient received oral corticosteroid therapy with rapid improvement. Conclusion To our knowledge, this is the first report of LPP following hepatitis A vaccination, among adults and children.